Legal Comparison Of Prostitution Arrangements In Indonesia And Sweden - Rr. Dijan Widijowati (Journal Research of Social Science, Economics, and Management, 2023)
Prostitution is one of the social problems that occur in Indonesia. Currently the perpetrators of prostitution have been among teenagers, students, students, housewives, and various other circles. The problem of prostitution is clearly not an easy problem to solve, and it cannot be denied that it continues to emerge with various modus operandi in society and develops along with the progress of the times, science and technology. The purpose of this study is to find out how the criminal law policy is against the parties that involved in the protitution crime in Indonesia and to figure out how the criminal law policy is against prostitution services users in Sweden. The method used is normative legal research. This research approach uses a comparative approach. Source of data comes from secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The conclusions in this study indicate that the current regulation of criminal law against the crime of prostitution has not been able to accommodate the problems of prostitution in Indonesia and it is necessary to establish new rules governing the crime of prostitution. The regulations regarding prostitution in Sweden are different from those in Indonesia. considering that the Swedish state enforces laws and regulations governing the crime of prostitution as contained in the Sex Purchase Law, and the Swedish government has also established a special investigative agency in the field of prostitution.